Part-time employment of gynecologists and obstetricians: a sub-group analysis of a Germany-wide survey of residents - Schott, Sarah; Eismann, Sabine (Archives of gynecology and obstetrics, 2017)
Background: Combining family and career is increasingly taken for granted in many fields. However, the medical profession in Germany has inadequately developed structures. Little is known regarding the satisfaction of physicians working part-time (PT). Methods: This Germany-wide on-line survey collected information on the working situation of PT employees (PTE) in gynecology. An anonymous questionnaire with 95 items, nine of which concerned PT work, was sent to 2770 residents and physicians undergoing further specialist training. Results: Of the 481 participants, 104 (96 % female, 4 % male) stated they worked PT, which is greater than the national average. 94 % of all women and 60 % of all men would work PT for better compatibility between work and family life. The PTE regularly work night shifts (NS) (96 %) and weekends (98 %). The number of monthly NS (median 5-9) was not different between the full-time (FT) employees and the PTE who work >75 %. Only when the working hours are reduced by 25 % or more, there are fewer NS (median 1-4) PTE that have a desire for fewer NS. The classic PT model is seldom realized; over 70 % of PTE work whole days, while other working models do not play a major role in Germany. On-call models were subjectively declared to have the best family friendly work-life balance. Outlook: The results obtained indicated that structures must be developed that to address the problem of childcare and the long working hours to ensure comprehensive medical care from specialists.